Association of owner related and external factors with micro and small manufacturing enterprises growth in Ethiopia - Tesfaye Ginbare Gutu; Abebe Shentema Yali (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
This study was conducted with the objective of analyzing the association of owner related and external factors with growth of MSEs operating in the manufacturing sector. Primary data were collected from 218 randomly selected owner/operator of manufacturing MSEs and coordinators of MSEs by using structured questionnaire and interview, respectively. Chi-square test was employed to analyze the owner related/internal factors, and external factors with growth of manufacturing MSEs. The statistical test revealed that gender, initial investment size, modern machinery, training, infrastructure and location have statistically significant association with growth of manufacturing MSEs; whereas age, education level, work premises and market linkage/ access are found to have statistically insignificant association with growth of MSEs operating in the manufacturing sector, though they make difference on the MSEs growth level. Therefore, to improve the growth of manufacturing MSEs, MSEs development office in collaboration with the municipality, among others, should consider the statistically significant factors and focus on the MSEs’ challenges which are stated by the owners of the business (own working premise and market access/linkage) and take corrective actions. Finally, further research on similar area is suggested by considering factors that need solution such as previous experience of operator in the sector, firm age and access to credit; besides similar study on remaining MSEs sector and comparative study may be conducted even within the manufacturing sector as economic sub-sector (i.e., textile and garment, metal working workshop, furniture and wood working, manufacturing bricks etc.) in order to have a holistic understanding of about the determinants of manufacturing MSEs growth